Temporomandibular Disorder sub-diagnosis as a possible cause of headache (Research, Society and Development, 2021)
Temporomandibular Disorder (TMD) encompasses abnormalities in the temporomandibular joint and/or masticatory muscles having headache as the most common symptom. This study aims to compare the prevalence of TMD in headache patients with the average prevalence of TMD in population. The prevalence ratio (PR) was 0,17 (95% CI 0,05-0,52; p